If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -19 = 2x + 12 Reorder the terms: -19 + 5x = 2x + 12 Reorder the terms: -19 + 5x = 12 + 2x Solving -19 + 5x = 12 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -19 + 5x + -2x = 12 + 2x + -2x Combine like terms: 5x + -2x = 3x -19 + 3x = 12 + 2x + -2x Combine like terms: 2x + -2x = 0 -19 + 3x = 12 + 0 -19 + 3x = 12 Add '19' to each side of the equation. -19 + 19 + 3x = 12 + 19 Combine like terms: -19 + 19 = 0 0 + 3x = 12 + 19 3x = 12 + 19 Combine like terms: 12 + 19 = 31 3x = 31 Divide each side by '3'. x = 10.33333333 Simplifying x = 10.33333333
| 21/57 | | f(x)=x(2x-1)(x+4) | | 2sin(x)=2-3cos^2(x) | | 40-19=3(x-4) | | 8-72y=95-15y | | 7x^2+2x-15=0 | | Y(1-x)DX+x(1+y)dy=0 | | 2t+4u=40 | | 27-17=5(x-8) | | 20x-16=18x+6 | | -(13+g)=-9 | | 61+4y-28=15y-9-4y | | 80=91x | | 2.9y+1.7=3.5+23y | | -2(-3x-1)-3=-4 | | 9y-9=7y+1 | | x+18+4x=-48-4x-51 | | 4(7x+5)-48x=10x-10 | | 9p+8q=108 | | 6x-12=4(x+7) | | 2cos^2(x)-4cos(x)=0 | | (9x^2-7)*(9x^2+7)= | | 2/9-3 | | 8P+4Q=68 | | x^2+ln(-x+4)= | | 2(x+5)=8is | | 25s^2-81=0 | | 13=5-13+3c | | 2x+-5y+9=0 | | 13=5+4a | | 7428=p*6 | | 13-5=4a |